Antiplatelet Prophylaxis Reduces the Risk of Early Hepatic Artery Thrombosis Following Liver Transplantation in High-Risk Patients - Iulia Minciuna; Iulia Minciuna; Iulia Minciuna; Jeroen De Jonge; Caroline Den Hoed; Raoel Maan; Wojciech G. Polak; Robert J. Porte; Harry L. A. Janssen; Harry L. A. Janssen; Bogdan Procopet; Bogdan Procopet; et al. (Transplant International)
The prevention of hepatic artery thrombosis (HAT) is pivotal for graft survival immediately after liver transplantation (LT). This study aimed to identify risk factors (RF) for early HAT (eHAT) and assess the benefit of antiplatelet prophylaxis (AP). This retrospective single-center study included 836 adult patients who underwent LT between 2007 and 2022. AP was administered for 3 months in N = 127 patients for surgical reasons. In total, 836 patients underwent LT, of whom 5.5% developed eHAT. In multivariable analysis, arterial anastomotic redo (aHR = 4.33), arterial reconstruction (aHR = 3.72) and cryptogenic liver cirrhosis (aHR = 4.25) were independent RFs for eHAT and AP appeared to be protective (aHR = 0.18). Indeed, in patients with at least one RF who received AP (RF+AP+, n = 94), the eHAT rate was significantly lower (3.2% vs. 21.3%, p < 0.001) than in those with RF who did not receive AP (RF+AP−, n = 89). The effect was even more pronounced when focusing on surgical RF alone (i.e., redo and/or reconstruction) with an additional improvement in 1 year graft survival of 85.3% vs. 70.4%, p = 0.02. AP did not pose an increased risk of bleeding. In conclusion, the main RFs for eHAT include arterial anastomotic redo, arterial reconstruction and cryptogenic liver cirrhosis as LT indications. Our results suggest that AP may protect against eHAT development in these high-risk patients.